IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE AHP DALAM MENENTUKAN TINGKAT KEPUASAN PELANGGAN (STUDIKASUS: DINAS KOPERASI, USAHA KECIL DAN MENENGAH KABUPATEN DELI SERDANG) - Laphita Sari Simanjuntak; , Jijon Raphita Sagala (Universitas Methodist Indonesia, 2018)
In order to increase customer satisfaction at Deli Serdang SME Corner, a study was conducted on the level of customer satisfaction in Deli Serdang SME Corner. To find out the extent to which UKM UKM's capabilities provide satisfaction through product, service, financial, shipping and company conditions, marketing research information from the results of marketing research is needed to find out the attitudes and behavior of customers towards what is most influential in making decisions at SME Corner customers Office of Cooperatives, Small and Medium Enterprises in Deli Serdang Regency. This research starts from the stage of analyzing existing systems that are obtained from direct interviews with related parties and observations. While the design method uses the Unified Modeling language (UML) to describe system design. In this case, to calculate the level of customer satisfaction, the AHP (Analytical Hierarchy Process) method is used. Using a decision-making system can provide convenience for Deli Serdang's UKM Corner to determine customer satisfaction in improving the quality to determine the level of customer satisfaction that is applied using PHP and MySQL Database programming .. The system was developed using a software engineering approach, including analysis, design and implementation . At the analysis stage, process analysis, input analysis, output analysis, ongoing system weakness analysis and needs analysis are carried out.